Experimental investigation of mechanical behavior of horseshoe-shaped segmental tunnel linings - Xufeng Ai; Wenge Qiu; Jihui Chen; Partab Rai; Yuchao Zheng; Hui Hu (Scientific Reports)
Abstract The fully mechanized tunnelling method using an earth pressure balance tunnel boring machine (EPB-TBM) with a horseshoe-shaped cross section was first developed and applied to a loess mountain tunnel, along with the application of a horseshoe-shaped segmental tunnel lining. The mechanical behavior of this novel type of segmental tunnel lining still contained uncertainties, and full-scale ring tests were conducted for further investigation. During the loading process, the ring deformation, joint opening, and concrete strain were measured, and the occurrence and progression of structural damage were observed and documented. The experimental results demonstrate that the structural failure of the horseshoe-shaped segmental ring mainly occurred in the arch area, while the invert did not prove to be a weak area. The deformation and failure mechanisms of the horseshoe-shaped segmental ring were found to be similar to those of circular ones. Significantly, the specific characteristics of the ring convergence deformation and bending moment distribution were significantly affected by the distribution positions of segment joints. In addition, during the initial stages of TBM advancement, frequent segment damage was observed at inferior joints, and the elaboration on the causes and corresponding measures was provided. This study provides significant evidence for the design and optimization of horseshoe-shaped segmental tunnel linings.